Reconstruction of southeast Tibetan Plateau summer climate using tree ring δ18O: moisture variability over the past two centuries - M. Pierre; Z. Li; M. Stievenard; S.-G. Hou; C. Risi; Q.-B. Zhang; V. Daux; C. Shi; V. Masson-Delmotte (Climate of the Past, 2012)
A tree-ring δ18O chronology of Linzhi spruce, spanning from AD 1781 to 2005, was developed in Bomi, Southeast Tibetan Plateau (TP). During the period with instrumental data (AD 1961–2005), this record is strongly correlated with regional CRU (Climate Research Unit) summer cloud data, which is supported by a precipitation δ18O simulation conducted with the isotope-enabled atmospheric general circulation model LMDZiso. A reconstruction of a regional summer cloud index, based upon the empirical relationship between cloud and diurnal temperature range, was therefore achieved. This index reflects regional moisture variability in the past 225 yr. The climate appears drier and more stable in the 20th century than previously. The drying trend in late 19th century of our reconstruction is consistent with a decrease in the TP glacier accumulation recorded in ice cores. An exceptional dry decade is documented in the 1810s, possibly related to the impact of repeated volcanic eruptions on monsoon flow.